Book review: Speculative fabulations in the ruins of colonial topographies: a (messy) review of ‘developing place-responsive pedagogy in outdoor environmental education: a rhizomatic curriculum autobiography’: by Alistair Stewart. - Mcphie, Jamie (Journal of Adventure Education and Outdoor Learning, 2020)
There are fundamental differences between the various ontologies of Australian First Nations peoples who have lived there for 40-60,000 years and the various ontologies of more recent Australian arrivals from the 18th Century onwards (peoples of European descent or Asian descent, for example).